The last Bolívar: resignation and retirement from power (1829-1830). Between authority and legality - Acevedo Tarazona, Álvaro; Villamizar, Carlos Iván (Universidad Pedagógica y Tecnológica de Colombia, 2015)
In the epistolary documents mailed by Bolívar, through the notionsof retirement and resignation, we will identify the political positions that Bolívar adopted in his letters regarding the exercise of power,in order to point out how these positions inluenced the political life of Colombian society at the time, and thus, understand hisbehaviors regarding the inevitable dissolution of the project of Colombian Nation during 1829- 1830. This work was developed through the analysis of hiscorrespondance from the time, from which the political positions formulated by Bolívar were extracted, in relation to his permanence or retirement from the presidential position.